Effectiveness of Case-Based Learning Versus Traditional Lectures on Clinical Reasoning Skills in Undergraduate Medical Students - Nudrat Sohail, Lubna Aslam, Andleeb Arshad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Clinical reasoning is a fundamental component of medical education and is essential for accurate diagnosis and appropriate patient management. Conventional lecture-based teaching is widely used but often promotes passive learning and may be insufficient for developing higher-order clinical reasoning skills. Case-based learning (CBL) has been proposed as an interactive instructional approach that enhances analytical reasoning by integrating theoretical knowledge with real-life clinical scenarios. Objective: To compare the effectiveness of case-based learning and traditional lecture-based teaching in improving clinical reasoning skills among undergraduate medical students. Methods: This quasi-experimental comparative study was conducted from January 2021 to February 2022 at an undergraduate medical college. A total of 80 undergraduate medical students in the clinical phase of training were included and divided into two groups: case-based learning (CBL; n = 40) and lecture-based learning (LBL; n = 40). Both groups were taught the same subjects over an identical period using different instructional approaches. Clinical reasoning skills were assessed before and after the intervention using a structured and validated assessment tool. Data were analyzed using paired and independent t-tests, with a p-value ≤ 0.05 considered statistically significant. Results: Both groups demonstrated comparable baseline clinical reasoning scores. Post-intervention scores showed significant improvement in both groups (p < 0.001). However, the improvement was significantly greater in the CBL group compared to the LBL group (mean post-test score: 72.4 ± 7.8 vs. 62.3 ± 8.1; p < 0.001). Conclusion: Case-based learning is more effective than traditional lecture-based instruction in improving clinical reasoning skills among undergraduate medical students. Incorporating case-based learning into undergraduate medical curricula may better prepare students for clinical practice by promoting active learning and critical thinking. Keywords: Case-based learning, Lecture-based learning, Clinical reasoning, Undergraduate medical education, Teaching methods.